Histomorphological and biochemical studies in experimental fluvanilate toxicity in rabbits - BANSAL, NEELAM; SHARMA, S K; SRIVASTAVA, A K; ROY, K S (The Indian Journal of Animal Sciences, 2013)
The histomorphological alteralions during subacute toxicity of fluvanilate was investigated in rabbits. Its effect on blood cholinesterase enzyme was also determined. Following daily oral administrations of fluvanilate (20/mg/kg) for 15 days. there was no significant alteration in blood cholinesterase. The main histomorphological alterations were: exfoliation of spennatogenic cells: degeneration of the glomeruli and tubular epithelium. islets of Langerhans and neurons: necrosis of hepatocytes and mononuclear cell infilteration in lung.